Text classification with an efficient preprocessing technique for cross-language and multilingual data - Khan, Towhid; Mallick, David Dew; Khan, Md.Shakiful Islam; Hasan, Md Mahadi (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.